Extent, distribution and origin of non-native forest tree species in Europe. Issue 7 (3rd October 2019) - Brus, Robert; Pötzelsberger, Elisabeth; Lapin, Katharina; Brundu, Giuseppe; Orazio, Christophe; Straigyte, Lina; Hasenauer, Hubert
ABSTRACT: The management of non-native tree species in European forests has a long history, but the information on the current number and geographic distribution of these species in European forests is incomplete and scattered across various datasets. This study aims to perform an inventory of the most frequent non-native tree species growing in European forests and analyse their current extent, geographic distribution and geographic origin. Our results show that at least 150 non-native tree species are currently growing in European forests and provenance trials. The genera represented by largest number of species are Eucalyptus, Pinus, Acacia and Abies . Species growing at the largest areas are Robinia pseudoacacia (2.44 million ha), Eucalyptus globulus (1.46 million ha), Picea sitchensis (1.16 million ha) and Pseudotsuga menziesii (0.83 million ha). In total, non-native tree species in Europe are found in an area of approximately 8.54 million ha, or 4.0% of the European forest area, and the five most abundant species account for up to 77% of this area. The largest number of these 150 species were introduced from North America (71), followed by Asia (45) and Australia (20). North American species occupy by far the largest area.